Evaluation of the Diagnostic Value of Non-criteria Antibodies for Antiphospholipid Syndrome Patients in a Chinese Cohort - Hu, Chaojun; Li, Siting; Xie, Zhijuan; You, Hanxiao; Jiang, Hui; Shi, Yu; Qi, Wanting; Zhao, Jiuliang; Wang, Qian; Tian, Xinping; Li, Mengtao; Zhao, Yan; et al. (Frontiers in Immunology, 2021)
Objective： Although specific anti-phospholipids antibodies (aPLs) have been used in the diagnosis of the antiphospholipid syndrome (APS) for years, new biomarkers are required to increase its diagnostic as well as risk-predictive power. This study aimed to explore the value of several extra-criteria aPLs in a Chinese cohort. Methods： Totally 312 patients including 100 patients diagnosed with primary APS, 51 with APS secondary to SLE, 71 with SLE, and 90 health controls were recruited. Serum anticardiolipin (aCL) IgG/IgM/IgA, anti-β2-glycoprotein I (aβ2GPI) IgG/IgM/IgA, anti-phosphatidylserine/prothrombin antibodies (aPS/PT) IgG/IgM, anti-annexin A5 antibodies (aAnxV) IgG/IgM were tested using ELISA kits. Results： Totally 30.46% and 6.62% of patients with APS were positive for aCL or aβ2GPI IgA respectively, while 39.07% and 24.50% were positive for aAnxV or aPS/PT for at least one antibodies (IgG or IgM). The addition test of aCL IgA and aAnxV IgM assist in identifying seronegative APS patients, and IgG aANxV was linked with stroke. Conclusion： Detection of aCL IgA, aβ2GPI IgA, aAnxV IgG/M, and aPS/PT IgG/M as biomarker provide additive value in APS diagnosis, and would help in risk prediction for APS patients in medical practice.